Revealing the Potency of Cinnamon as an Anti-cancer and Chemopreventive Agent - Yonika Arum Larasati; Edy Meiyanto (Indonesian Society for Cancer Chemoprevention, 2018)
Cinnamon (Cinnamomum spp.), an ancient spice, has been explored as a potential for medicinal purposes. Despite numerous studies about its potency in overcoming of numerous diseases, the potency as anti-cancer would be a challenge. This current article provides a review of the anti-cancer and chemoprevention potency of cinnamon and its major constituents: cinnamaldehyde, cinnamic acid, 2-hydroxycinnamaldehyde, 2-methoxycinnamaldehyde, and eugenol. Comprehensively, cinnamon and its constituents exhibit the anti-cancer and cancer prevention activities through various mechanisms: (1) anti-proliferation, (2) induction of cell death, (3) anti-angiogenesis, (4) anti-metastasis, (5) suppression of tumor-promoted inflammation, (6) immunomodulation, and (7) modulation of redox homeostasis; both in vitro and in vivo. Moreover, cinnamon also shows the synergistic anti-cancer effect with well-known anti-cancer drugs, such as doxorubicin, which support its potency to be used as a combination chemotherapeutic (co-chemotherapeutic) agent. However, further study should be established to determine the exact target molecule(s) of cinnamon in the cancer cells.Keywords: cinnamon, spice, cancer, anti-cancer, chemopreventive